PROSPECTS FOR THE USE OF ROSE HIPS IN FOOD TECHNOLOGY - Saribaeva, Dilorom; Atamirzaeva, Sohiba; Kayumova, Asalxon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
A morphological study of 5 types of rose hips for use in the food industry was carried out. For comparison, we took the species growing in the Namangan region: dog rose (Rosa canina L.), Kokand (Rosa kokanica.Regel), Fedchenko (Rosa fedtschenkoana Regel), Begger (Rosa beggeriana Schrenk), corymbifera (Rosa corymbifera Borkh.). The organoleptic and physico-chemical parameters of a biologically active additive of different varieties of rosehip were studied, the pre-prepared fruits were separated from the seeds and extracted with water and ethyl alcohol.